2016
DOI: 10.1080/17483107.2016.1218554
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of activities of daily living in virtual environments with intuitive user interface and force feedback

Abstract: The system can potentially be used as a tool to complement conventional rehabilitation approaches of ADL. Implications for rehabilitation Rehabilitation of activities of daily living can be facilitated using computer-assisted approaches. The existing approaches focus on cognitive training rather than the manual skills. A virtual training system with intuitive user interface and force feedback was designed to improve the learning of the manual skills. The study shows that system could be used as a training tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…The scientific evidence shows statistically significant results in the groups treated with virtual reality, leading to considerable changes in the affected upper limb functionality [ 40 , 59 , 60 , 61 , 62 ]. As is observed in a previous study about the effect of Virtual Reality compared to conventional physiotherapy on upper limb function in children with OBP [ 40 ], Virtual Reality Mirror Therapy combined with Armeo Spring™ Pediatric (Hocoma AG, Switzerland) resulted in improvements at the level of mobility and affected upper limb strength, obtaining higher scores on the Mallet scale, being significantly more effective than conventional therapy and achieving the main objective of restoring basic functionality to the affected upper limb abilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scientific evidence shows statistically significant results in the groups treated with virtual reality, leading to considerable changes in the affected upper limb functionality [ 40 , 59 , 60 , 61 , 62 ]. As is observed in a previous study about the effect of Virtual Reality compared to conventional physiotherapy on upper limb function in children with OBP [ 40 ], Virtual Reality Mirror Therapy combined with Armeo Spring™ Pediatric (Hocoma AG, Switzerland) resulted in improvements at the level of mobility and affected upper limb strength, obtaining higher scores on the Mallet scale, being significantly more effective than conventional therapy and achieving the main objective of restoring basic functionality to the affected upper limb abilities.…”
Section: Discussionmentioning
confidence: 99%
“…As is observed in a previous study about the effect of Virtual Reality compared to conventional physiotherapy on upper limb function in children with OBP [ 40 ], Virtual Reality Mirror Therapy combined with Armeo Spring™ Pediatric (Hocoma AG, Switzerland) resulted in improvements at the level of mobility and affected upper limb strength, obtaining higher scores on the Mallet scale, being significantly more effective than conventional therapy and achieving the main objective of restoring basic functionality to the affected upper limb abilities. Virtual reality has also been used for the rehabilitation of activities of daily living using a virtual environment, obtaining a positive effect as a complementary tool to conventional rehabilitation [ 60 ]. The results obtained in this study, that is, the improvements in functionality (independent tasks and the use of the affected hand with grasp) assessed with the CHEQ questionnaire [ 49 , 50 ], could be transferred to certain activities of daily living, such as personal hygiene, leisure, and sports activities.…”
Section: Discussionmentioning
confidence: 99%
“…Transferring of the training in activity of daily living (ADL): many studies suggested the potential offered by ecological tasks to transfer the results of re-learning of cognitive and motor abilities that were damaged in ADL. Positive impact of ecological tasks on ADL is documented by many studies ( Laver et al, 2015 ; Chiang et al, 2017 ).…”
Section: Methodsmentioning
confidence: 97%
“…This system is simple to use, requires limited instrumentation and a short training. Several studies have shown that VR can produce a significant clinical impact and most of them have focused on the use of VR as an assessment tool, while some others show impact on rehabilitation training of cognitive, motor, social, and daily life functions ( Standen and Brown, 2005 ; Keshner and Weiss, 2007 ; Optale et al, 2010 ; Wuang et al, 2011 ; Man et al, 2012 ; Climent-Martínez et al, 2014 ; Simões et al, 2014 , 2018 ; Chiang et al, 2017 ). VR is acquiring increasing credibility as a useful tool for teaching independent living skills to persons with Intellectual Disability (ID) in a safe environment; furthermore, generalization into real environments of skills acquired during VR training seems to be feasible ( Cromby et al, 1996a , b ; Brown et al, 1998 , 1999 ; Standen et al, 1998 , 2001 ; Gourlay et al, 2000 ; Mendozzi et al, 2000 ; Brooks et al, 2002 ; Groenewegen et al, 2008 ; Josman et al, 2008 ; Saiano et al, 2015 ; Yang et al, 2016 ; Simões et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%